Islamic Carpet Decorations in Persian Manuscript Illustrations (Al-Academy, 2024)
This research, entitled "A Study of Islamic Carpet Decorations and Their Appearance in Persian Manuscript Illustrations," consists of four chapters. The first chapter deals with the research problem, its importance, and the need for it, as well as defining the most important terms used in it.There are some questions related to the possibility of relying on manuscript illustrations as a primary source for studying carpet decoration. The most important questions: Do the decorations in the carpet drawings in the manuscript illustrations represent the actual designs of Iranian carpets? Was the illustrator sufficiently familiar with these designs?The second chapter includes the theoretical framework and two sub-sections: the first on decoration in carpets, the second on the origin of Islamic carpets. The third chapter deals with the research procedures and the analysis of the research sample, including the research community and the research tool. The fourth chapter focuses on the results, conclusions, and recommendations.